Some Identities of the Degenerate Multi-Poly-Bernoulli Polynomials of Complex Variable. (2nd June 2021) - Muhiuddin, G.; Khan, W. A.; Duran, U.; Al-Kadi, D.
Abstract : In this paper, we introduce degenerate multi-poly-Bernoulli polynomials and derive some identities of these polynomials. We give some relationship between degenerate multi-poly-Bernoulli polynomials degenerate Whitney numbers and Stirling numbers of the first kind. Moreover, we define degenerate multi-poly-Bernoulli polynomials of complex variables, and then, we derive several properties and relations.